The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fpls.2023.1226064
|View full text |Cite
|
Sign up to set email alerts
|

Critical weather limits for paddy rice under diverse ecosystems of India

Abstract: Rice yields are largely influenced by variability in weather. Here, we demonstrate the effect of weather variables viz., maximum and minimum temperatures, rainfall, morning and evening relative humidity, bright sunshine hours on the yield of rice cv. Swarna, grown across five rice ecologies of India through field experiments during kharif (wet) season (Jun-Sept.). Critical thresholds of weather elements were identified for achieving above average, average and below average yield for each ecology. The investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Similarly, for August, the corresponding figure is 0.04%, and a similar value was also observed for rainfall in September. Adequate and timely June rainfall is essential for proper germination, transplanting, and early growth stages of the rice crop; August rains help rice in the crucial reproduction stage of its crop cycle (Bal et al, 2023). As shown above, the sensitivity of rice yield to June and August rainfall is critical due to the declining trend in monsoon rainfall observed in the region (Saha and Ghosh, 2019).…”
Section: Short Communicationmentioning
confidence: 98%
“…Similarly, for August, the corresponding figure is 0.04%, and a similar value was also observed for rainfall in September. Adequate and timely June rainfall is essential for proper germination, transplanting, and early growth stages of the rice crop; August rains help rice in the crucial reproduction stage of its crop cycle (Bal et al, 2023). As shown above, the sensitivity of rice yield to June and August rainfall is critical due to the declining trend in monsoon rainfall observed in the region (Saha and Ghosh, 2019).…”
Section: Short Communicationmentioning
confidence: 98%
“…The Kobayashi et al (2010) concluded that higher air temperature and incident radiation tend to advance anthesis in rice. Thus, delayed transplanting forced the crop to pass through a relatively lower temperature regime during its reproductive phase (Bal et al, 2023). They also reported significant variation in rice yield in response to weather variabilities during different growth phases of the crop under the diverse ecosystems of India.…”
Section: Effect Of Preponing Sowing Dates On Yield Attributes and Yie...mentioning
confidence: 99%
“…The month-wise rainfall distribution pattern is given in Figure 2. May is the warmest summer month of the year with a daily maximum temperature of 37-41°C, while the coldest winter month is January with a daily minimum temperature of 5-8°C in January (Bal et al, 2023). Although December, January, and February are the main winter months, temperature decreases significantly from November.…”
Section: Climate Soil and Cropping Systemmentioning
confidence: 99%
“…The 2010) concluded that higher air temperature and incident radiation tend to advance anthesis in rice. Thus, delayed transplanting forced the crop to pass through a relatively lower temperature regime during its reproductive phase (Bal et al, 2023). They also reported significant variation in rice yield in response to weather variabilities during different growth phases of the crop under the diverse ecosystems of India.…”
Section: Effect Of Preponing Sowing Dates On Yield Attributes and Yie...mentioning
confidence: 99%